Genomic Insights into Mollusk Terrestrialization: Parallel and Convergent Gene Family Expansions as Key Facilitators in Out-of-the-Sea Transitions - Arístide, Leandro (2023)
Animals abandoned their marine niche and successfully adapted to life on land multiple times throughout evolution, providing a rare opportunity to study the mechanisms driving large scale macroevolutionary convergence. However, the genomic factors underlying this process remain largely unknown. Here, we investigate the macroevolutionary dynamics of gene repertoire evolution during repeated transitions out of the sea in mollusks, a lineage that has transitioned to freshwater and terrestrial environments multiple independent times. Through phylogenomics and phylogenetic comparative methods, we examine ∼100 genomic data sets encompassing all major molluskan lineages. We introduce a conceptual framework for identifying and analyzing parallel and convergent evolution at the orthogroup level (groups of genes derived from a single ancestral gene in the species in question) and explore the extent of these mechanisms. Despite deep temporal divergences, we found that parallel expansions of ancient gene families played a major role in facilitating adaptation to nonmarine habitats, highlighting the relevance of the preexisting genomic toolkit in facilitating adaptation to new environments. The expanded functions primarily involve metabolic, osmoregulatory, and defense-related systems. We further found functionally convergent lineage-exclusive gene gains, while family contractions appear to be driven by neutral processes. Also, genomic innovations likely contributed to fuel independent habitat transitions. Overall, our study reveals that various mechanisms of gene repertoire evolution - parallelism, convergence, and innovation - can simultaneously contribute to major evolutionary transitions. Our results provide a genome-wide gene repertoire atlas of molluskan terrestrialization that paves the way toward further understanding the functional and evolutionary bases of this process.